The synergy of marine fishing and the eco-tourism sector as the solution in resolving poverty of fishermen - Sunarlan Sunarlan; Kusnadi Kusnadi (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The socio-economic condition of the traditional fishermen in Blimbingsari Village is considered to be less than the optimum. This problem has happened due to the diminishing revenue from fishing activities. The opportunity to work in the oﬀ-fishing sectors available are also limited, thus this creates a problem for thefishermen when it comes to earning an additional income. The objective of this article is to explore the alternative economic resources’ potential, with the aim of increasing the fishermen's revenue, to overcome poverty, and to improve their welfare. This study used a qualitative method to analyse the data. The results of the study reveal that the diminishing revenue of the fishermen is caused by the scarcity of the fishery resources, the unstable weather conditions that aﬀect the ability to sail, and the limited seafaring coverage. On the other hand, the marine eco-tourism sector may have the opportunity to assist in the improvement of the business diversification of fishing. Although the marine eco-tourism sector is running at a limited capacity, this sector is able to accommodate the development of tourism services. The fishermen's family members are able to be involved in their business activities. For instance, by becoming a helper in the fish stall business or even having the chance to establish their own business. The need for a fish supply for the fish stall business can be obtained from the local fishermen. Therefore, a mutual synergy between the eco-tourism and fishing sectors can be created by involving village-owned business, particularly when it comes to organising the local economic potential. This synergy can provide the chance to develop economic opportunities at a wider range. The rearrangement of the coastal area is also necessary to provide an opportunity for the local people to participate in coastal-based economic activities.